Climbing up the ladder and watching out for the fall: Poverty dynamics in rural Bangladesh - Ahmed, Akhter; Tauseef, Salauddin (International Food Policy Research Institute, 2019)
This paper analyzes poverty dynamics in rural Bangladesh using a nationally representative panel dataset of 5,260 rural households interviewed in 2011/12 and 2015. We find that education, savings, assets, non-farm employment, substantial safety net transfers, and women’s empowerment are key factors in breaking persistent poverty; and savings, non-farm engagement, and substantial safety net transfers prevent households from falling into poverty. The results are consistent across multinomial logit, logit, and simultaneous quantile regression models. Thus, policies and programs that address the determinants of persistent and transient poverty identified in this study hold promise for sustained poverty reduction in rural Bangladesh.